Phenolic Compounds and Antioxidant Status of Cookies Supplemented with Apple Pomace - Marek Kruczek; Dorota Gumul; Anna Korus; Krzysztof Buksa; Rafał Ziobro (MDPI AG, 2023)
The post-production leftovers after the pressing of apple juice are a rich source of health-promoting compounds, which could be used in the food industry for the manufacture of dietary foods, applicable also for people with celiac disease. This raw material is currently little used, and the cost of its disposal is considerable. Therefore, an attempt was made to enrich gluten-free cookies with different proportions of apple pomace. The content of individual polyphenols determined by the UPLC-PDA-MS/MS method, basic chemical composition, physical properties of cookies with 15%, 30%, 45%, and 60% apple pomace, were evaluated. It was found that apple pomace in gluten-free cookies caused an increase in the content of phenolic acids, quercetin derivatives, flavan-3-ols and dihydrochalcones. An elevation in protein, fat, and minerals was also observed. The growing share of apple pomace caused a significant increase in the content of total fiber, soluble, and insoluble fractions, but resulted in an increase in the hardness and darkening of the cookies while reducing their volume.